Age-independent association between high-sensitivity C-reactive protein and blood pressure in middle-aged adults - Zhao, Huijun; Lu, Yiwen; Niu, Junjie; Bian, Hong; Kuang, Xingya (Vojnosanitetski pregled, 2023)
Background/Aim. There is growing evidence suggesting that high-sensitivity C-reactive protein (hs-CRP) is a reliable biomarker in patients with hypertension. While the relationship between hypertension and age is well established, the connection between hs-CRP and age remains unclear. The aim of the study was to determine a relationship between hs-CRP and age, body mass index (BMI), and blood pressure in middle-aged people. Methods. This cross-sectional survey was conducted in Shanghai, China, and it included data from 1,677 healthy male participants aged 18 to 50 years and 1,127 healthy female participants aged 19 to 49 years recruited during routine health examinations. The hs-CRP, BMI, systolic blood pressure (SBP), and diastolic blood pressure (DBP) were recorded. Results. The participants were first separated into four age quartile groups, in which an increase in BMI, SBP, and DBP was observed but not in hs-CRP. Afterward, the participants were divided into four hs-CRP quartile groups, in which an increase in BMI, SBP, and DBP was noted, but not in age. Finally, using Pearson correlation, positive correlations were found between hs-CRP, BMI, SBP, and DBP, but no correlation was discovered between age and hs-CRP. Conclusion. The authors showed that age is likely a confounding factor that correlates with SBP, DBP, and BMI, but it does not directly correlate with hs-CRP.